OPTIMALISASI CANVA SEBAGAI STRATEGI PEMASARAN PRODUK BAGI PELAKU UMKM JAJANAN TRADISIONAL - Herdawati, Herdawati; Hafid, Hardianti (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Small, and Medium Enterprises (SME) play a crucial role in both the global and local economies, including in Indonesia. One popular type of MSME is traditional snack businesses, which hold high cultural value and unique flavors. However, traditional snack SME often encounter challenges in marketing their products, especially due to limited access and knowledge of social media and graphic design skills. In addressing these challenges, the use of Canva as a graphic design tool becomes relevant. This research aims to deepen the utilization of Canva in enhancing sales promotion for traditional snack SME, particularly in Makassar City. Through literature review and needs identification, training and implementation of Canva were conducted for one traditional snack MSME in Makassar. The results show that SME have successfully improved their knowledge and skills in using Canva, resulting in more attractive and professional promotional materials. Collaboration among SME also played a significant role in the successful implementation of Canva. Although there are still challenges to be addressed, the use of Canva has great potential in supporting the growth and sustainability of traditional snack SME. Therefore, the utilization of Canva as a product marketing strategy for traditional snack SME is worthy of further exploration and expansion.